\(A=\frac{1}{\sqrt{5}-\sqrt{3}+2}\)
\(A=\frac{1}{\left(\sqrt{5}+2\right)+\sqrt{3}}\)
\(A=\frac{1\left(\left(\sqrt{5}+2\right)-\sqrt{3}\right)}{\left(\left(\sqrt{5}+2\right)+3\right)\left(\left(\sqrt{5}+2\right)-\sqrt{3}\right)}\)
\(A=\frac{\sqrt{5}+2-\sqrt{3}}{\left(\sqrt{5}+2\right)^2-3}\)
\(A=\frac{\sqrt{5}+2-\sqrt{3}}{6-4\sqrt{5}}\)
\(A=\frac{\left(\sqrt{5}+2-\sqrt{3}\right)\left(6+4\sqrt{5}\right)}{\left(6-4\sqrt{5}\right)\left(6+4\sqrt{5}\right)}\)
\(A=\frac{6\sqrt{5}+20+12+8\sqrt{5}-6\sqrt{3}-4\sqrt{15}}{36-16\cdot5}\)
\(A=\frac{14\sqrt{5}+32-6\sqrt{3}-4\sqrt{15}}{-44}\)
\(A=\frac{6\sqrt{3}+4\sqrt{15}-14\sqrt{5}-32}{44}\)
Nhớ k cho mik đó nha ....... rồi kb lun ahihi